La crise ordinaire: Les ménagères montréalaises et la crise des années trente - Baillargeon, Denyse (Labour/Le Travailleur, 1992)
Abstract This article analyzes the contribution of Montréal working-class women to the family economy during the Depression of the 1930s and shows the impact of this unprecedented crisis on the different components of their domestic work. It is based on interviews with thirty women who married before 1934. Their testimonies reveal the extent of certain phenomenon such as the use of contraceptive methods and the paid work of women within the home and illustrate the extreme poverty in which they lived even before the Depression struck. Thus, for many of them, the period was nothing but a new episode in their struggle for survival.